(untitled) (Journal of Computational Mathematics, 1999)
This paper deals with the asymptotic stability of theoretical solutions and numerical methods for the delay differential equations (DDEs) where a, b_1, b_2, ... b_m and y_0 C, 0 < λ_m λ_m-1 ... λ_1